Virus detection and identification using random multiplex (RT)-PCR with 3'-locked random primers - Eaton John W; Telang Sucheta; Sims Jonathan; Clem Amy L; Chesney Jason (Virology Journal, 2007)
Abstract Background PCR-based detection and identification of viruses assumes a known, relatively stable genome. Unfortunately, high mutation rates may lead to extensive changes in viral nucleic acid sequences making dedicated PCR primer use problematic. Furthermore, in bioterrorism, viral consensus sequences can be genetically modified as a countermeasure to RT-PCR and DNA chip detection. Accordingly, there is a great need for the development of rapid and universal virus detection and identification technologies. Results We report herein that viral genomic DNA or RNA can be separated from host nucleic acids in plasma by filtration and nuclease digestion, and randomly amplified in a single PCR using a mixture of primers designed to be resistant to primer-dimer amplification (5'-VVVVVVVVAA-3', V = A, G or C; 38 or 6561 primers). We have termed this novel PCR method Random Multiplex (RT)-PCR since hundreds of overlapping PCR amplifications occur simultaneously. Using this method, we have successfullydetected and partially sequenced 3 separate viruses in human plasma without using virus-specific reagents (i.e., Adenovirus Type 17, Coxsackievirus A7, and Respiratory Syncytial Virus B). The method is sensitive to ~1000 genome equivalents/ml and may represent the fastest means of detection of unknown viruses. Conclusion These studies suggest that the further development of random multiplex (RT)-PCR may lead to a diagnostic assay that can universally detect viruses in donated blood products as well as in patients suffering with idiopathic disease states of possible viral etiology.